Three Melodramas by Pietro Metastasio - Metastasio, Pietro, 1698-1782 (Book collections on Project MUSE., 1981)
Pietro Antonio Domenico Trapassi (1698--1782) was an Italian poet and librettist, considered the most important writer of opera seria libretti. In this volume, Pietro Metastasio presents new translations of Dido Abandoned, Demetrius, and The Olympiad that stay close to the original form and wording. Featuring an introduction that highlights the playwright's life and significant innovations in dramatic technique as well as a short bibliography, Fucilla's translations will be of interest not only to literary scholars, but also to those concerned with the history of music.